Al-‘Ilāj al-Nafsī ‘inda al-Ḥakīm al-Tirmidzī; Dirāsah Naqdiyah li ‘Ilm Nafs al-Sulūkī - Muhammad Faqih Nidzom; Rohmah Akhirul Mukharom (Universitas Darussalam Gontor, 2022)
In modern society, the development and progress of technology have impacted various psychological problems. While Modern Psychology, especially Behavior, has not been able to provide a solution, so needed a concept to provide solutions to human psychological problems; tahdzibun nafs is a concept to human psychiatric issues. This psychotherapy concept differs from the others, and it uses the concept of tahdzibun nafs, and Hakim Tirmidzi is one of the Sufi scholars who do not mix with western thought. This research uses the Sufism approach, which aims to explore the concept of psychotherapy according to judge Tirmidhi based on inner experience and his understanding of the Quran and hadith. He explains the concept of tahdzibun nafs to overcome human psychiatric problems. The Concept requires one to reach the level of Lubb in the level of heart, which consists of sadr, qalb, fuad, and lubb using tahliyah nafs, takhliyah nafs, tajliyah nafs to achieve nafs muthmainnah. It’s because the source of mental health lies in the healthy heart that always loves God.